2008
DOI: 10.1007/s11064-008-9649-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Ischemia-Mediated Cell Death in Neonatal Rat Brain

Abstract: The examination of Bcl-2-associated X protein (Bax) protein's role in the activation of cognate nuclear, mitochondrial and ER cell death signaling cascades and the resulting effects on cell death phenotype in the brain after neonatal hypoxia-ischemia (HI) requires an understanding of neonatal HI insult and progression, as well as, its dysfunctional outcomes. In addition, knowledge of key concepts of oxidative stress, a major injurious component of HI, and the different cell death phenotypes (i.e. apoptosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 124 publications
(175 reference statements)
4
45
0
2
Order By: Relevance
“…Due to the variation in the Atg7 suppression achieved between different transfection experiments using siRNA (see text), similar data obtained from three replicate experiments were not combined for quantification here. Asterisks indicate time points where there was a significant difference between nRNA and siAtg7 populations (*P \ 0.001, **P \ 0.01, ***P \ 0.001) Caspase-independent cell death following H 2 O 2 insult requires autophagic machinery in C57/Black 6 J cortical neurons Acute oxidative stress, such as that following ischemic reperfusion injury during stroke can invoke a necrotic-like cell death that is devoid of caspase activity at the core or center of infarction [23,24,42]. We have previously shown that following acute H 2 O 2 insult, cortical neurons from C57 Black/6 J mice undergo programmed necrosis (PCDtype III) that is independent of effector caspase activity (specifically caspase-3 and caspase-7) [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the variation in the Atg7 suppression achieved between different transfection experiments using siRNA (see text), similar data obtained from three replicate experiments were not combined for quantification here. Asterisks indicate time points where there was a significant difference between nRNA and siAtg7 populations (*P \ 0.001, **P \ 0.01, ***P \ 0.001) Caspase-independent cell death following H 2 O 2 insult requires autophagic machinery in C57/Black 6 J cortical neurons Acute oxidative stress, such as that following ischemic reperfusion injury during stroke can invoke a necrotic-like cell death that is devoid of caspase activity at the core or center of infarction [23,24,42]. We have previously shown that following acute H 2 O 2 insult, cortical neurons from C57 Black/6 J mice undergo programmed necrosis (PCDtype III) that is independent of effector caspase activity (specifically caspase-3 and caspase-7) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis has previously been defined as a programmed or regulated type of cell death, characterized by the activation of caspases, while necrosis has been thought of as a caspase-independent, unregulated process. However, contemporary evidence supports the thesis that neuronal PCD is not exclusively apoptotic; rather it is a multifaceted phenomenon that encompasses autophagy and programmed necrosis, with extensive crosstalk between the three death pathways [22][23][24]. Within a given population of neurons, it is thought that multiple PCD pathways can be invoked concurrently in response to a single injury or insult [25].…”
Section: Introductionmentioning
confidence: 99%
“…4 Other physiological or pharmacological effects such as heat, hypoxia, ischemia, disease, glucose and metabolic starvation, and changes in lipid metabolism are also potent inducers of the ER stress pathway. 35 ER stress has been implicated in a number of diseases including ischemia/reperfusion of the brain and heart, 35,68 heart failure, 35 and diabetes, 69 with the UPR activated in cardiac tissues by decreases in ATP, ER Ca 2ϩ , or UDPglucose. 70 In the heart, hypoxia, ischemia/reperfusion, hypertrophy, pressure overload, and drug-induced insults can result in activation of ER stress.…”
Section: Er Stress In the Heartmentioning
confidence: 99%
“…comes are multifaceted within a holistic framework of interplay between multiple injury mechanisms, often operating in parallel [43][44][45] (Fig. 1).…”
Section: Mitochondrial Respiratory Complexes Oxidative Damage and Pcdmentioning
confidence: 99%